Analytical approaches to examine gamma-aminobutyric acid and glutamate vesicular co-packaging - Kim, SeulAh; Sabatini, Bernardo L. (Frontiers in Synaptic Neuroscience, 2023)
Multi-transmitter neurons, i.e., those that release more than one type of neurotransmitter, have been found in many organisms and brain areas. Given the peculiar biology of these cells, as well as the potential for diverse effects of each of the transmitters released, new tools and approaches are necessary to parse the mechanisms and functions of synaptic co-transmission. Recently, we and others have studied neurons that project to the lateral habenula and release both GABA and glutamate, in some cases by packaging both transmitters in the same synaptic vesicles. Here, we discuss the main challenges with current electrophysiological approaches to studying the mechanisms of glutamate/GABA co-release, a novel statistical analysis that can identify co-packaging of neurotransmitters versus release from separate vesicle, and the implications of glutamate/GABA co-release for synapse function and plasticity.